Characterization and Biosynthesis of Silver Nanoparticles by Clove Extract and its Application to Bacteria - Mamoon, Maream; Shamran, Zaid Taleb; Yassin, Heba Khlaf (American Journal of Biology and Natural Sciences, 2025)
This study investigates the synthesis of silver nanoparticles (AgNPs) using clove extract (Syzygium aromaticum), a plant known for its rich bioactive compounds. The research evaluates the physicochemical properties and antibacterial effects of the synthesized nanoparticles. Clove extract, abundant in phenolic compounds like eugenol, functions as both a reducing and stabilizing agent in converting silver ions (Ag⁺) into silver nanoparticles. The synthesis process involved mixing the clove extract with silver nitrate and applying heat, resulting in a noticeable color change to brown, indicative of nanoparticle formation. The presence of silver nanoparticles was confirmed using UV-Vis spectroscopy, which displayed a characteristic peak at 438 nm, corresponding to the surface plasmon resonance (SPR) of AgNPs. Fourier transform infrared (FTIR) spectroscopy was utilized to identify the functional groups involved in the synthesis and stabilization of the nanoparticles. Scanning electron microscopy (SEM) provided insights into the size distribution of the AgNPs, which ranged from 9.8 nm to 27.6 nm, suggesting a high surface area and reactivity suitable for antimicrobial applications. The antibacterial activity of the synthesized AgNPs was assessed against Enterococcus and Escherichia coli (E. coli) by measuring the inhibition zones. The results demonstrated significant antibacterial effects, with inhibition zones measuring 18 mm for Enterococcus and 20 mm for E. coli. These findings underscore the potential of silver nanoparticles derived from clove extract as effective antimicrobial agents.